CREDIT RISK MANAGEMENT AND FINANCIAL PERFORMANCE OF COMMERCIAL BANKS: A CASE STUDY OF EQUITY BANK MUKONO BRANCH. - Leatitia Kavira Tsongo (Uganda Christian University, 2025)
This study examined the effect of credit risk management on the financial performance of commercial banks, focusing on Equity Bank Mukono Branch. The objectives of the study were to analyze the effectiveness of credit assessment practices, examine the role of loan monitoring mechanisms, and evaluate the impact of credit risk mitigation strategies such as risk-based pricing and loan restructuring on financial performance. The study adopted a quantitative cross-sectional descriptive design. The target population consisted of 35 employees in the credit and finance departments, from which a sample of 32 respondents was selected using Krejcie and Morgan’s table. Data were collected using structured questionnaires, tested for validity and reliability, and analyzed using descriptive statistics, including means and standard deviations, with results presented in tables. The key findings revealed that effective loan monitoring significantly enhances financial performance, although weaknesses were observed in loan recovery teams and approval monitoring processes. Credit assessment practices, including risk data collection and portfolio evaluation, were found to positively influence profitability, though gaps in early warning systems and risk concentration identification remained. Credit risk mitigation strategies such as loan restructuring, enforcement of penalties, and credit limits contributed positively to financial stability, while prioritization of loyal customers and moderate use of risk-based pricing were less effective. Financial performance indicators, including net profit margin, return on assets (ROA), and return on equity (ROE), showed improvements, though with variations in perceptions among respondents. viii The study concluded that robust loan monitoring, reliable credit assessment, and well-implemented mitigation strategies are essential for strengthening financial performance. It recommended that Equity Bank enhance loan recovery efficiency, improve monitoring approval processes, strengthen early warning systems, and benchmark best practices in credit appraisal. Additionally, the bank should continue to apply restructuring and penalty enforcement while refining risk-based pricing models to align interest rates with risk levels. The study further recommended caution in prioritizing loyal customers, ensuring repayment capacity remains the basis for lending decisions.
Undergraduate research